2005
DOI: 10.1191/0269215505cr819oa
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low back pain in traumatic lower limb amputees

Abstract: Low back pain in amputees is a significant problem equal to that of pain in the phantom limb and a biomechanical (myofascial) rather than a degenerative aetiology is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 26 publications
5
108
1
7
Order By: Relevance
“…20 However, it is unknown if this general state of symmetry in the lateral abdominal muscles is true for persons with unilateral lower extremity amputation. Previous researchers 11 have suggested that symmetry should not be assumed, and side-to-side differences have been noted in the size of the psoas muscle in those with lower extremity amputations. Side-to-side differences in the thickness and function of the lateral abdominal wall muscles are a reasonable possibility, considering asymmetric weight distribution in the limbs, an altered center of gravity, and alterations in daily functional activities, including gait for those ambulating with a prosthetic limb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 However, it is unknown if this general state of symmetry in the lateral abdominal muscles is true for persons with unilateral lower extremity amputation. Previous researchers 11 have suggested that symmetry should not be assumed, and side-to-side differences have been noted in the size of the psoas muscle in those with lower extremity amputations. Side-to-side differences in the thickness and function of the lateral abdominal wall muscles are a reasonable possibility, considering asymmetric weight distribution in the limbs, an altered center of gravity, and alterations in daily functional activities, including gait for those ambulating with a prosthetic limb.…”
Section: Discussionmentioning
confidence: 99%
“…One study by Kulkarni et al 11 included magnetic resonance imaging of the lumbar spine on persons with lower extremity amputations with and without LBP. Though an incidental finding of the study, the authors note that in all 20 subjects with TFA (regardless of the presence of LBP) there was marked hypertrophy of the psoas muscle on the intact limb along with atrophy on the amputated side.…”
Section: Discussion Tmentioning
confidence: 99%
See 1 more Smart Citation
“…These impairments may include decreases in strength, proprioception, and balance; as well as gait deviations and pain [4][5][6][7]. These patients are often referred to physical therapy in order to address their physical impairments and to obtain independence with prosthetic use during ambulation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a leg length discrepancy resulting in a hip hike during ambulation makes the amputee more susceptible to secondary low back pain symptoms. Early prosthetic gait training and postural muscle exercises have the potential to prevent amputees from becoming disabled by chronic back pain [7]. Free swing gait training is a technique sometimes utilized by physical therapists during treatment of transfemoral amputees learning to use prosthesis.…”
Section: Introductionmentioning
confidence: 99%